The Federative Approach to Data Governance and Management in an Open Information Systems Environment A Case Study on Data Governance and Management of Clinical Breast Cancer Treatment Data - Meriläinen, Daniel (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
The Master’s thesis aims to show that the theoretical framework of the federative approach is understandable and workable. The goal is to answer the research questions as follows. The main research question is how the theoretical framework of data federation works in practice. This is done by comparing the data federation and the golden record concepts. In order to support the main question, two sub-questions are introduced. The first sub-question concerns what the benefits of the framework are. The second sub-question concerns what the limitations of the framework are. In the theory section I argue that user organizations have lost control over the data models they use and partly also over their data. The data are increasingly external and provided as a service, with unknown data models, APIs and/or adapters. Yet, the ability to manage and federate data is becoming continuously important for organizations in order to benefit from digital data. To manage and federate data effectively, it is necessary to know why the federated data sets have been created, for what purposes they are used, and why the data are stored. I compare two ontological approaches. The two approaches are studied theoretically by reflecting the phenomenon against the existing literature on ontologies and data governance. The findings show that contextual metadata is needed in order to introduce the data federations of the technical and informational metadata within ISs. Data federation starts from understanding the contextual metadata. The avoidance of data deficiencies relating to the human perception of real word states, the representations of the real world in data/ISs and their combined effects must also be considered when data are federated. An artifact based on the matrix was designed to conceptualize data federation. The artifact operationalizes the considerations into questions, ranging from understanding the reason for data creation to agreeing the governance accountabilities for the data. The Master’s thesis has the certain limitations relating to the conceptual sources. Initially data federation based on shared and cross- referenced attributes may be tedious and time-consuming, but once done, there is no need to repeat it. The background of the Master’s thesis is based on five years of relevant research. In spite of the relatively long research period there is as yet a limited amount of empirical, publicly available data to support the federative approach. This also applies the artifact designed in this case study. The federative approach may increase value creation along with overall IT investments and improve data governance. The necessary investments are recommendable in order to focus on data attributes and MDM tools with the stance of interoperability. Data federation creates a new approach to integration with the aid of MDM tools. Thus it is not necessary to have a new IS, as mappings are already available. This is an important finding since IT expenses in organizations are apt to skyrocket when overlapping systems and appliances are acquired

Tutkimustyö pyrkii osoittamaan, että data federaation teoreettinen viitekehys on ymmärrettävä. Tutkimuksen pääkysymys on, miten teoreettinen viitekehys toimii käytännössä. Vertaan kahta ontologista lähestymistapaa, tutkimuksen teoreettista kontekstuaalista viitekehystä ja kanonista golden record-konseptia keskenään. Pääkysymyksen tueksi olen valinnut kaksi alakysymystä:. 1. Mitkä ovat viitekehyksen hyödyt ja 2. Mitkä ovat viitekehyksen rajoitteet. Teoriaosuudessa väitän, että käyttäjäorganisaatiot ovat menettäneet käyttämiensä datamallien hallinnan ja osittain myös hallinnan käyttämiinsä tietoihin. Data on yleensä ulkoistettua palvelua, jossa käytetään yritykselle vieraita datamalleja. Kuitenkin kyky hallita ja yhdistää tietoa on yhä tärkeämpää yrityksille digitaalisen datan hyödyntämiseksi. Jotta dataa voidaan tehokkaasti hallita ja yhdistää, on tiedettävä miksi yhdistetyt aineistot on luotu, mihin tarkoituksiin niitä käytetään ja miksi aineistoja tallennetaan. Kahta ontologista lähestymistapaa on tutkittu teoreettisesti reflektoimalla ilmiötä vastaavaan kirjallisuuteen ontologioiden ja tiedonhallinnan perspektiivistä käsin. Tulokset osoittavat, että kontekstuaalinen metadata on välttämätön, jotta datafederaatio on ylipäätään mahdollista toteuttaa tietojärjestelmän teknisen ja informatiivisen metadatan kontekstissa. Siksi datafederaatio edellyttää kontekstuaalisen metadatan syvällistä ymmärtämistä. Dataan perustuvien vajavaisuuksien välttäminen, joka liittyy inhimilliseen käsitykseen todellisesta tiedosta edellyttää puolestaan, että reaalimaailman esittäminen tietojärjestelmissä ja niistä johtuvat yhteisvaikutukset ovat tarpeellisia huomioida datafederaatiota toteutettaessa. Tapaustutkimuksen kaksiulotteiseen matriisin perustuva artefakti suunniteltiin datafederaation käsitteellistämiseksi. Artefakti huomioi kaikki ne kysymykset, jotka liittyvät datan luomisen syihin ja niiden ymmärtämiseen sekä datan hallintavastuusta sopimiseen. Pro gradu omaa tietyt rajoitteet liittyen konseptuaalisiin lähteisiin. Tutkielman taustatiedot perustuvat soveltuvin osin viisi vuotta kestäneeseen TEKES-rahoitteiseen tutkimukseen. Huolimatta suhteellisen pitkästä tutkimusajasta käytettävissä on vielä vain rajoitetusti empiiristä ja julkaisukelpoista tietoa tukemaan datafederaatiota. Tämä koskee myös tapaustutkimusta varten suunniteltua artefaktia. Datafederaatio voi lisätä arvonluontia kokonaisvaltaisten IT investointien yhteydessä ja parantaa datan hallintaa. Datafederaatiota tukevat investoinnit ovat suositeltavia kohdistaa data-attribuutteihin ja MDM työkaluihin yhteen toimivuuden näkökulmasta katsottuna. Datafederaatio luo uuden tulokulman datan integroimiseen MDM työkalujen avulla. Tästä johtuen uusien tietojärjestelmien hankinta on tarpeetonta, koska attribuutteihin liittyvät kartoitukset ovat useimmiten jo saatavilla organisaation olemassa olevissa tietojärjestelmissä. Tämä on tapaustutkimuksen merkittävä havainto, koska organisaatioiden IT kustannuksilla on usein taipumusta ylittää investointibudjetti hankittaessa päällekkäisiä järjestelmiä ja laitteita.